Micro-vascular complications in diabetic patient’s of type-2 diabetes mellitus - Yogi, KN (Journal of Institute of Medicine Nepal, 2009)
Background: A hospital based prosopective study conducted in 11000 beded teaching hospital of a metropolitan city Islamabad, Pakistan, two group of patients having diabetes for < 5 years and > 5 years were evaluated and investigated for micro-vascular complications from January to December of 2006. Material and Methods: A total of 100 patients were included in the study. Result: Among them 72% patients of diabetes < 5 years and 76% patients of diabetes>5 years are overweight, most of them were having very high glycosylated haemoglobin and 48% has had neuropathy, 66% has had nephropathy and 72% has had retinopathy respectively. Conclusion: This study once again proved that increasing age, overweight, uncontrolled blood sugar, and high level of glycosylated haemoglobin all contributes to higher rates of micro-vascular complications. Similar types of study if conducted in Nepal will be more useful for health professionals and researcher in future. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 49-58